Does Being A Cancer Patient or Family Caregiver of A Cancer Patient Affect Stem Cell Donation Awareness? - Gulcan Bagcivan; Nurten Ozen; Damla Bayrak; Fatma Ilknur Cinar (Elsevier, 2020)
Objective: One of the most difficult challenges regarding hematopoietic stem cell transplantation in Turkey is finding donors for allogeneic transplantation candidates who do not have related donors. This study aims to determine whether there is any difference in the awareness of stem cell donation and transplantation between cancer and noncancer patients and their family caregivers. In addition, this study aims to determine the awareness of stem cell donation and transplantation in the entire study population. Methods: This descriptive study was conducted in Turkey using a data collection form comprising questions about demographics, stem cell transplantations, donations, and medical history. On analyzing the research data, variables were expressed as mean ± standard deviation and as numbers (n) and percentages (%). The Chi-square and Fisher's exact tests were performed to evaluate differences among cancer and noncancer diagnosed patients and their family members. Results: A total of 192 patients and 169 family caregivers participated in the study. In comparison with noncancer patients, cancer patients showed more awareness on what stem cell transplantation is, how lifesaving it is, and how to donate stem cells. Similarly, the family caregivers of cancer patients were more aware of what stem cell transplantation is and how to donate stem cells. Conclusions: The results of this study showed that cancer patients and their families were more aware of stem cell donation and transplantation; however, most of the patients and families did not know enough about the national registry program and how to donate stem cells.